Complete genome sequence of Alicyclobacillus acidocaldarius type strain (104-IAT). Issue 1 (January 2010) - Mavromatis, Konstantinos; Sikorski, Johannes; Lapidus, Alla; Glavina Del Rio, Tijana; Copeland, Alex; Tice, Hope; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; Bruce, David; Goodwin, Lynne; et al.
Abstract Alicyclobacillus acidocaldarius (Darland and Brock 1971) is the type species of the larger of the two genera in the bacillal family 'Alicyclobacillaceae '.A. acidocaldarius is a free-living and non-pathogenic organism, but may also be associated with food and fruit spoilage. Due to its acidophilic nature, several enzymes from this species have since long been subjected to detailed molecular and biochemical studies. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first completed genome sequence of the family 'Alicyclobacillaceae '. The 3, 205, 686 bp long genome (chromosome and three plasmids) with its 3, 153 protein-coding and 82 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.